Analysis of Polycerate Mutants Reveals the Evolutionary Co-option of HOXD1 for Horn Patterning in Bovidae. (2nd February 2021) - Allais-Bonnet, Aurélie; Hintermann, Aurélie; Deloche, Marie-Christine; Cornette, Raphaël; Bardou, Philippe; Naval-Sanchez, Marina; Pinton, Alain; Haruda, Ashleigh; Grohs, Cécile; Zakany, Jozsef; Bigi, Daniele; Medugorac, Ivica; et al.
Abstract: In the course of evolution, pecorans (i.e., higher ruminants) developed a remarkable diversity of osseous cranial appendages, collectively referred to as "headgear, " which likely share the same origin and genetic basis. However, the nature and function of the genetic determinants underlying their number and position remain elusive. Jacob and other rare populations of sheep and goats are characterized by polyceraty, the presence of more than two horns. Here, we characterize distinct POLYCERATE alleles in each species, both associated with defective HOXD1 function. We show that haploinsufficiency at this locus results in the splitting of horn bud primordia, likely following the abnormal extension of an initial morphogenetic field. These results highlight the key role played by this gene in headgear patterning and illustrate the evolutionary co-option of a gene involved in the early development of bilateria to properly fix the position and number of these distinctive organs of Bovidae.